Wybrane aspekty logistycznej sprawności produktu jako źródła wartości dodanej - wyniki badań - Bielecki, Maciej; Hanczak, Magdalena; Skoczylas, Aleksandra (Wydawnictwo Politechniki Łódzkiej, 2016)
Logistics challenges in the twenty-first century clearly show the need to consider newer and newer conditions, in order to improve the effectiveness and efficiency of the flows of goods and information about them. One of these elements, indicated by the authors is the product itself. Features and characteristics of the product determine, because the nature of logistic processes, which often must be tailored to the specifics of particular goods. Presented monograph highlights the potential that lies in the possibilities of design and modify products, and the supreme advantage should be pro-logistics approach. Monograph "Selected aspects of the logistics efficiency of the product, as a source of added value - the test results" presents the results of preliminary research on the issue of logistics efficiency of the product and indicates the places where the application of the concept of delivering added value not only the company but the ultimate recipients [...].
Selected aspects of the logistics efficiency of the product, as a source of added value - the test results
Na okładce wykorzystano zdjęcie ze strony: https://freerangestock.com/photos
Red. nauk. Wydziału Organizacji i Zarządzania: Lewandowski, Jerzy.
Keywords: rola produktu w procesach logistycznych; logistyczna sprawność produktu; podatność transportowa; logistics; flows of goods; logistic processes; logistics efficiency of the product; added values